Pyridoxamine Limits Cardiac Dysfunction in a Rat Model of Doxorubicin-Induced Cardiotoxicity - Sibren Haesen; Manon Marie Jager; Aline Brillouet; Iris de Laat; Lotte Vastmans; Eline Verghote; Anouk Delaet; Sarah D'Haese; Ibrahim Hamad; Markus Kleinewietfeld; Jeroen Mebis; Wilfried Mullens; et al. (MDPI AG, 2024)
The use of doxorubicin (DOX) chemotherapy is restricted due to dose-dependent cardiotoxicity. Pyridoxamine (PM) is a vitamin B6 derivative with favorable effects on diverse cardiovascular diseases, suggesting a cardioprotective effect on DOX-induced cardiotoxicity. The cardioprotective nature of PM was investigated in a rat model of DOX-induced cardiotoxicity. Six-week-old female Sprague Dawley rats were treated intravenously with 2 mg/kg DOX or saline (CTRL) weekly for eight weeks. Two other groups received PM via the drinking water next to DOX (DOX+PM) or saline (CTRL+PM). Echocardiography, strain analysis, and hemodynamic measurements were performed to evaluate cardiac function. Fibrotic remodeling, myocardial inflammation, oxidative stress, apoptosis, and ferroptosis were evaluated by various in vitro techniques. PM significantly attenuated DOX-induced left ventricular (LV) dilated cardiomyopathy and limited TGF-β1-related LV fibrotic remodeling and macrophage-driven myocardial inflammation. PM protected against DOX-induced ferroptosis, as evidenced by restored DOX-induced disturbance of redox balance, improved cytosolic and mitochondrial iron regulation, and reduced mitochondrial damage at the gene level. In conclusion, PM attenuated the development of cardiac damage after DOX treatment by reducing myocardial fibrosis, inflammation, and mitochondrial damage and by restoring redox and iron regulation at the gene level, suggesting that PM may be a novel cardioprotective strategy for DOX-induced cardiomyopathy.